Oxidative stress induced by oxime reactivators of acetylcholinesterase in vitro. (April 2019) - Muckova, L.; Vanova, N.; Misik, J.; Herman, D.; Pejchal, J.; Jun, D.
Abstract: In this study, we determined the effect of methoxime (MMB-4), asoxime (HI-6), obidoxime (LüH-6), trimedoxime (TMB-4), and pralidoxime (2-PAM) on redox homeostasis in vitro. Cultured human hepatoma cells (HepG2) were exposed to oximes at concentrations equivalent to their IC50 (assessed using MTT assay) and evaluated 1, 4 and 24 h after incubation. Additionally, intact, early and late apoptotic and necrotic cells were quantified by microcapillary flow cytometry. Intracellular levels of oxygen/nitrogen species were determined using two fluorescent probes (2′, 7′-dichlorodihydrofluorescein diacetate and dihydroethidium). Malondialdehyde and 3-nitrotyrosine were measured by LC-MS/MS. Non-protein thiols and non-protein disulfides were evaluated using HPLC-UV to reflect antioxidant capacity. Oxidative and nitrosative stress was induced by LüH-6, TMB-4 and MMB-4, whereas 2-PAM and HI-6 appeared as weak oxidative stressors with no activity towards nitrosative stress in HepG2 cells. Based on these results, bisquartenary oxime reactivators containing two functional oxime groups at the position 4 of pyridinium ring appear as more intense oxidative and nitrosative inducers. Activation of apoptosis and necrosis do not seem to correlate with generation of RONS. On the other hand, both processes rather reflect MDA concentrations, i.e. the damage of biomolecules. Highlights: Assessment of oxime reactivators as inducers of oxidative/nitrosative stress in HepG2 cells. Capability of oximes to induce RONS declines in the following order: LüH-6 > TMB-4 > MMB-4 > 2-PAM > HI-6. Oxime groups at the C4 position of bispyridinium oximes seems to stimulate oxidative and nitrosative stress more effectively. The length and the nature of carbon linker between pyridinium rings seems to further modify the ability to induce RONS.